Arsenic association with circulating oxidized low-density lipoprotein in a Native American community. Issue 13 (3rd July 2018) - Harmon, Molly E.; Lewis, Johnnye; Miller, Curtis; Hoover, Joseph; Ali, Abdul-Mehdi S.; Shuey, Chris; Cajero, Miranda; Lucas, Selita; Pacheco, Bernadette; Erdei, Esther; Ramone, Sandy; Nez, Teddy; et al.
ABSTRACT: More than 500 abandoned uranium (U) mines within the Navajo Nation contribute U, arsenic (As) and other metals to groundwater, soil and potentially air through airborne transport. The adverse cardiovascular health effects attributed to cumulative exposure to these metals remains uncertain. The aim of this study was to examine whether environmental exposure to these metals may promote or exacerbate the oxidation of low-density lipoprotein (LDL) cholesterol in this Native American population. The correlation of cardiovascular biomarkers (oxidized LDL (oxLDL) and C-reactive protein (CRP)) from a Navajo cohort ( n  = 252) with mean annual As and U intakes from water and urine metals was estimated using linear regression. Proof-of-concept assays were performed to investigate whether As and U directly oxidize human LDL. Mean annual As intake from water was positively and significantly associated with oxLDL, but not CRP in this study population, while U intake estimates were negatively associated with oxLDL. In an acellular system, As, but not U, directly oxidized the apolipoprotein B-100 component of purified human LDL. Neither metal promoted lipid peroxidation of the LDL particle. Both the population and lab results are consistent with the hypothesis that As promotes oxidation of LDL, a crucial step in vascular inflammation and chronic vascular disease. Conversely, for outcomes related to U, negative associations were observed between U intake and oxLDL, and U only minimally altered human LDL in direct exposure experiments. Only urine U was correlated with CRP, whereas no other metals in water or urine were apparently reliable predictors of this inflammatory marker.